Source rupture process, directivity and and Coulomb stress change of the 12 January 2010 (Port-au-Prince Haiti, Mw7.0) earthquake - Borges, JF (2010)
The Haiti earthquake occurred on Tuesday, January 12, 2010 at 21:53:10 UTC. Its epi- center was at 18.46 degrees North, 72.53 degrees West, about 25 km WSW of Haiti’s capital, Port-au-Prince, along the tectonic boundary between Caribbean and North America plate dominated by left-lateral stri- ke slip motion and compression with 2 cm/yr of slip velocity eastward with respect to the North America plate. The earthquake was relatively shallow (about 13 km depth) with Mw 7.0 and CMT mechanism solution indica- ting left-lateral strike slip movement with a fault plane oriented toward the WNW-ESE. More than 10 aftershocks ranging from 5.0 to 5.9 in magnitude struck the area in hours following the main shock. Most of these af- tershocks have occurred to the west of the mainshock in the Mirogoane Lakes region and its distribution suggests that the length of the rupture was around 70 km. Rupture velocity and direction was constrained by using the directivity effect determined from broad-band waveforms recorded at regio- nal and teleseismic distances using DIRDOP computational code (DIRectivity DOPpler effect) [1]. The Results show that the rup- ture spread mainly from WNW to ESE with a velocity of 2.5 km/s. In order to obtain the spatiotemporal slip distribution of a fi- nite rupture model we have used teleseismic body wave and the Kikuchi and Kanamori’s method [2]. The inversion show complex source time function with a total scalar seismic moment of 2.2 x 1019Nm (Mw=6.9) a source duration of about 18 sec with a main energy relesea in the first 13 sec. Finally, we compared a map of aftershocks with the Coulomb stress changes caused by the main shock in the region [3]. [1] Kikuchi, M., and Kanamori, H., 1982, Inversion of com- plex body waves: Bull. Seismol. Soc. Am., v. 72, p. 491-506. [2] Caldeira B., Bezzeghoud M, Borges JF, 2009; DIRDOP: a directivity ap- proach to determining the seismic rupture velocity vector. J Seismology, DOI 10.1007/ s10950-009-9183-x [3] King, G. C. P., Stein, R. S. y Lin, J, 1994, Static stress changes and the triggering of earthquakes. Bull. Seismol. Soc. Am. 84,935-953. More than 10 aftershocks ranging from 5.0 to 5.9 in magnitude struck the area in hours following the main shock. Most of these aftershocks have occurred to the west of the mainshock in the Mirogoane Lakes region and its distribution suggests that the length of the rupture was around 70 km. In order to obtain the spatiotemporal slip distribution of a finite rupture model we have used teleseismic body wave and the Kikuchi and Kanamori's method [1]. Rupture velocity was constrained by using the directivity effect determined from waveforms recorded at regional and teleseismic distances [2]. The spatiotemporal slip estimated points to a unilateral rupture that propagates from WNW to ESE with a rupture velocity of 2.5 km/s. Finally, we compared a map of aftershocks with the Coulomb stress changes caused by the event in the region [3]. [1]- Kikuchi, M., and Kanamori, H., 1982, Inversion of complex body waves: Bull. Seismol. Soc. Am., v. 72, p. 491-506. [2] Caldeira B., Bezzeghoud M, Borges JF, 2009; DIRDOP: a directivity approach to determining the seismic rupture velocity vector. J Seismology, DOI 10.1007/s10950-009-9183-x [3] -King, G. C. P., Stein, R. S. y Lin, J, 1994, Static stress changes and the triggering of earthquakes. Bull. Seismol. Soc. Am. 84,935-953.